2011
DOI: 10.1007/s10290-011-0094-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects at home of initiating production abroad: evidence from matched French firms

Abstract: Based on matching techniques in combination with a difference-in-difference estimator, this paper estimates the effects at home of initiating production abroad through the establishment of a foreign production affiliate. The analysis covers manufacturing and service firms active in France during the period 1987-1999. We show that the motivation to start producing abroad is an important determinant of its impact at home. Marketseeking foreign direct investment (FDI) in manufacturing is associated with significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 46 publications
5
79
3
Order By: Relevance
“…12 The impact on firm performance also depends on the type of investment. Horizontal investments guarantee positive gains in the labor growth rate, whereas vertical ones do not reduce employment, but do increase the capital to labor ratio, thanks to the reorganization of the production process 13 (Hijzen et al 2011). Dealing with a sample of Italian firms, Bronzini (2015) confirms the hypothesis of a better division of labor, in particular for those firms choosing complex strategies of internationalization.…”
Section: From Fdi To Performance: Ex Post Effects Of Fdisupporting
confidence: 61%
“…12 The impact on firm performance also depends on the type of investment. Horizontal investments guarantee positive gains in the labor growth rate, whereas vertical ones do not reduce employment, but do increase the capital to labor ratio, thanks to the reorganization of the production process 13 (Hijzen et al 2011). Dealing with a sample of Italian firms, Bronzini (2015) confirms the hypothesis of a better division of labor, in particular for those firms choosing complex strategies of internationalization.…”
Section: From Fdi To Performance: Ex Post Effects Of Fdisupporting
confidence: 61%
“…This empirical evidence suggests that when a quantifiable impact was found it most often tended to be small but positive (Bergsten, Horst, & Moran, 1978;Dunning & Lundan, 2008;Kojima, 1973;Kojima & Ozawa, 1984;Kokko, 2006;Lipsey, 2004;Ozawa, 1992). OFDI has been found to enhance growth and output (Herzer, 2008(Herzer, , 2010, exports (Chédor, Mucchielli, & Soubaya, 2002;Hijzen, Jean, & Mayer, 2011;Lipsey & Ramstetter, 2003), employment (Federico & Minerva, 2008;Hijzen et al, 2011), productivity and efficiency (Driffield & Love, 2005;Egger, Pfaffermayr, & Wolfmayr-Schnitzer, 2001;Sunesen, Jespersen, & Thelle, 2010;Van Pottelsberghe de la Potterie & Lichtenberg, 2001) and know-how (Globerman, Kokko, & Sjöholm, 2000;Herstad & Jónsdóttir, 2006;Popovici, 2005) in particular advanced home economies. These studies may only offer a limited amount of insight, given their focus on just a few countries or country groupings and obvious data limitations, arising, in particular, from the aggregate nature of some datasets which were used.…”
Section: Insights From the Theoretical And Empirical Literaturementioning
confidence: 99%
“…Examples of studies in this field include those by Navaretti and Castellani (2004), Castellani et al (2008), and Imbriani et al (2011) for Italian MNEs; Hijzen et al (2011) for French MNEs; Navaretti et al (2010) for French and Italian MNEs; Kleinert and Toubal (2007) for German MNEs;Ito (2015), Hijzen et al (2007), and Edamura et al (2011) for Japanese MNEs; Debaere et al (2010) for Korean MNEs; and Masso et al (2008) for Estonian MNEs. The econometric identification of the learning effect is one of the most important issues in this literature.…”
mentioning
confidence: 96%
“…Debaere et al (2010), Edamura et al (2011), andNavaretti et al (2010) classified FDI in developing and developed countries as VFDI and HFDI, respectively. Hijzen et al (2011) defined VFDI as investments in developing countries by firms in industries in which the investing country has a comparative disadvantage and HFDI as investments in developed countries by firms in industries in which the investing country has a comparative advantage. These studies found different effects on firms' performance in the home country according to FDI type.…”
mentioning
confidence: 99%